The expanding world of extracellular traps: not only neutrophils but much more - Goldmann, Oliver; Medina, Eva (Frontiers in Immunology, 2013)
The release of extracellular traps (ETs) is a recently described mechanism of innate immune response to infection. Although ETs have been intensely investigated in the context of neutrophil antimicrobial effector mechanisms, these structures can also be released by other immune cells such as mast cells, eosinophils and macrophages. The different ETs have several features in common, no matter from what type of cells they originated. Thus, all ETs comprise a DNA backbone with embedded antimicrobial peptides, proteases and histones. However, they also exhibit remarkable individual differences such as the subcellular compartments from where the DNA backbone originates (e.g. nucleus, mitochondria), the proportion of responding cells within the pool as well as the molecular mechanism underlying the ETs formation. This review summarizes the knowledge accumulated in recent years regarding the expanding and complex world of ETs and their role in the immune function with a particular focus on immune cells apart from neutrophils.